2019
DOI: 10.1093/jxb/erz516
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor TCP20 regulates peach bud endodormancy by inhibiting DAM5/DAM6 and interacting with ABF2

Abstract: The dormancy-associated MADS-box (DAM) genes PpDAM5 and PpDAM6 have been shown to play important roles in bud endodormancy; however, their molecular regulatory mechanism in peach is unclear. In this study, by use of yeast one-hybrid screening, we isolated a TEOSINTE BRANCHED1/CYCLOIDEA/PROLIFERATING CELL FACTOR transcription factor, PpTCP20, in the peach cultivar ‘Zhongyou 4’ (Prunus persica var. nectarina). The protein was localized in the nucleus and was capable of forming a homodimer. Electrophoretic mobili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 73 publications
1
26
0
Order By: Relevance
“…We also highlighted the site II motif associated with the sequence GCCCA. This element is recognized by TCP transcription factors described as down-regulators of PpeDAM5 and PpeDAM6 expression in peach (Wang et al, 2020). Site II motifs were identified in the intronic regions of all six PdoDAM genes and the promoters of PdoDAM3 and PdoDAM6, closely located to the one reported by the literature.…”
Section: Analysis Of Cis-regulatory Elements In Pdodam1-6 Regulatory supporting
confidence: 60%
“…We also highlighted the site II motif associated with the sequence GCCCA. This element is recognized by TCP transcription factors described as down-regulators of PpeDAM5 and PpeDAM6 expression in peach (Wang et al, 2020). Site II motifs were identified in the intronic regions of all six PdoDAM genes and the promoters of PdoDAM3 and PdoDAM6, closely located to the one reported by the literature.…”
Section: Analysis Of Cis-regulatory Elements In Pdodam1-6 Regulatory supporting
confidence: 60%
“…The SOC1 members of the DAM family participate in the dormancy and owering of apricot [44]; AtSOC1 has also been linked to oral organ development and early owering [45]. Recent studies have shown that PpTCP20 negatively regulates the expression of PpDAM5 and PpDAM6 to regulate the internal dormancy of peach blossom buds [46]. By inhibiting ABA biosynthesis, activating CK signal transduction and inducing cyclin expression, GhTCP19 promotes the dormancy release of gladiolus bulbs [47].…”
Section: Tfs Involved In Dormancy Releasementioning
confidence: 99%
“…Recent studies of DAM genes and their homologs SHORT VEGETATIVE PHASE-like (SVL) genes suggest they are cooperatively regulated by several transcription factors, hormones, and epigenetic factors (da Silveira Falavigna et al, 2018). Wang et al (2019) propose peach TEOSINTE BRANCHED1 transcription factor negatively regulates DAM5 and DAM6 expression, resulting in dormancy release . Leida et al (2012b) reported that histone modifications in DAM6 promoter, the second exon and the second intron are involved in dormancy release (Leida et al, 2012b).…”
Section: Introductionmentioning
confidence: 99%